Brasilia’s Database Administrators - Adriana, Jane (2016)
Database administration has gained an essential role in the management of new database technologies. Different data models are being created for supporting the enormous data volume, from the traditional relational database. These new models are called NoSQL (Not only SQL) databases. The adoption of best practices and procedures, has become essential for the operation of database management systems. Thus, this paper investigates some of the techniques and tools used by database administrators. The study highlights features and particularities in databases within the area of Brasilia, the Capital of Brazil. The results point to which new technologies regarding database management are currently the most relevant, as well as the central issues in this area.